Hierarchical host–guest assemblies formed on dodecaborate-coated gold nanoparticles. Issue 33 (11th April 2017) - Assaf, Khaleel I.; Hennig, Andreas; Peng, Shu; Guo, Dong-Sheng; Gabel, Detlef; Nau, Werner M.
Abstract : Undecahydro-mercapto- closo -dodecaborate (BSH ), a purely inorganic cluster anion, serves as an unconventional stabilizing ligand for the preparation of gold nanoparticles (AuNPs). Abstract : Undecahydro-mercapto- closo -dodecaborate (BSH ), a purely inorganic cluster anion, serves as an unconventional stabilizing ligand for the preparation of gold nanoparticles (AuNPs). The BSH-capped AuNPs serve as nano-scaffolds, allowing for the creation of supramolecular architectures by using polycationic macrocyclic host molecules, through strong host–guest complexation. An amphiphilic calixarene (CX) forms first mono- and subsequently bi-layer assemblies on the BSH–AuNP surfaces depending on the CX concentration. The inorganic–organic hybrid materials, combined with host–dye displacement assays, serve as a chemosensing ensemble for negatively charged molecules, including DNA.